2011
DOI: 10.5012/bkcs.2011.32.3.867
|View full text |Cite
|
Sign up to set email alerts
|

Development of Drug-Loaded PLGA Microparticles with Different Release Patterns for Prolonged Drug Delivery

Abstract: For the prolonged delivery and sustained release rates of low molecular weight drugs, poly(lactic-co-glycolic acid) (PLGA) microparticles containing the drug SKL-2020 have been investigated. On increasing polyvinyl alcohol (PVA) concentration (from 0.2% to 5%), the size of microparticles decreased (from 48.02 µm to 10.63 µm) and more uniform size distribution was noticeable due to the powerful emulsifying ability of PVA. A higher drug loading (from 5% to 20%) caused a larger concentration gradient between 2 ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
(7 reference statements)
1
6
0
Order By: Relevance
“…All porous MPs developed in this work were in the diameter range of 19–42 μm, which indicates that sufficient surface area will be available for A549 growth, since previously published works have shown that A549 cells have an average diameter of 6–15 μm [59, 60]. The standard deviations observed is typical of PLGA microspheres prepared using low amounts of PVA surfactant, as observed by other groups [6163]. Ideally, a pore diameter of 20 μm or greater is desirable for growth and infiltration of mammalian cells, while smaller pores provide adequate surface area for cell attachment on the surface [64, 65].…”
Section: Discussionsupporting
confidence: 75%
“…All porous MPs developed in this work were in the diameter range of 19–42 μm, which indicates that sufficient surface area will be available for A549 growth, since previously published works have shown that A549 cells have an average diameter of 6–15 μm [59, 60]. The standard deviations observed is typical of PLGA microspheres prepared using low amounts of PVA surfactant, as observed by other groups [6163]. Ideally, a pore diameter of 20 μm or greater is desirable for growth and infiltration of mammalian cells, while smaller pores provide adequate surface area for cell attachment on the surface [64, 65].…”
Section: Discussionsupporting
confidence: 75%
“…Nanotechnology brings unique characteristics to the system, which, in combination with PLGA's unique features, allow for extensive biomedical applications. It is possible to encapsulate both organic and inorganic materials into PLGA, such as small-molecule drugs [2,12], vaccines [13], proteins [14,15] and metallic [16] as well as magnetic [17,18] nanoparticles (NPs). The methods of production of PLGA-based materials can be adapted to various types of drugs, making it possible to encapsulate hydrophobic and hydrophilic molecules and thus making this copolymer an ideal drug delivery system (DDS) [4].…”
Section: Introductionmentioning
confidence: 99%
“…As a drug delivery system, MPs offer many advantages such as the use of different administration routes or the opportunity of encapsulating different molecules including proteins (Ospina-Villa et al 2019 ) and nucleic acid (McKiernan et al 2018 ). In particular, MPs can be used for the controlled release of drugs (Choi et al 2011 ; Guo et al 2015 ) that can be modulated by choosing the kind of polymer and its chemical and molecular features such as molecular weight (MW), monomer composition (Takeuchi et al 2017 ), crystallinity, glass transition temperature ( T g ), and inherent viscosity (Ansary et al 2014 ). In this scenario, a lot of biodegradable polymers can be used to formulate MPs as alginate (Strobel et al 2020 ), dextran (Shah et al 2019 ), chitosan (Batista et al 2019 ), gelatin (da Silva and Pinto et al 2019 ) and poly-(lactic- co -glycolic acid) (PLGA) (Kapoor et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%